Smooth muscle and neural dysfunction contribute to different phases of murine postoperative ileus. Issue 6 (18th February 2016) - Farro, G.; Gomez‐Pinilla, P. J.; Di Giovangiulio, M.; Stakenborg, N.; Auteri, M.; Thijs, T.; Depoortere, I.; Matteoli, G.; Boeckxstaens, G. E.
Abstract: Background: Postoperative ileus (POI) is characterized by a transient inhibition of gastrointestinal (GI) motility after abdominal surgery mediated by the inflammation of the muscularis externa (ME). The aim of this study was to identify alterations in the enteric nervous system that may contribute to the pathogenesis of POI. Methods: Gastrointestinal transit, contractility of isolated smooth muscle strips and inflammatory parameters were evaluated at different time points (1.5 h to 10 days) after intestinal manipulation (IM) in mice. Immune‐labeling was used to visualize changes in myenteric neurons. Key Results: Intestinal manipulation resulted in an immediate inhibition of GI transit recovering between 24 h and 5 days. In vitro contractility to K + (60 mM) or carbachol (10 −9 to 10 −4 M) was biphasically suppressed over 24 h after IM (with transient recovery at 6 h). The first phase of impaired myogenic contractility was associated with increased expression of TNF‐α, IL‐6 and IL‐1α. After 24 h, we identified a significant reduction in electrical field stimulation‐evoked contractions and relaxations, lasting up to 10 days after IM. This was associated with a reduced expression of chat and nos1 genes. Conclusions & Inferences: Intestinal manipulation induces two waves of smooth muscle inhibition, most likely mediated by inflammatory cytokines, lasting up to 3 days after IM. Further, we here identify a late third phase (>24 h) characterized by impaired cholinergic and nitrergic neurotransmission persisting after recovery of muscle contractility. These findings illustrate that POI results from inflammation‐mediated impaired smooth muscle contraction, but also involves a long‐lasting impact of IM on the enteric nervous system. Abstract : We aimed to identify alterations in the enteric nervous system that may contribute to the pathogenesis of postoperative ileus. Surgical manipulation of the intestine induced two phases of muscle dysfunction over 24 h and a late prolonged phase of impaired neurotransmission. Our data show that intestinal surgery affect both muscle cells and neurons and different inflammatory mechanisms underlie the different phases.